Eficiência de adubação nitrogenada em diferentes estádios fenológicos da cultura do sorgo - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
The objective of the present work was to evaluate the effect of the application of nitrogen doses in different phenological stages of the sorghum culture on the morphological characteristics and production components. The experiment was conducted during the safer period of 2017 and 2018 at the Experimental Farm of the State University of Goiás - Camus Ipameri. The experimental design was a randomized block design, arranged in a 2 x 5 x 5 factorial scheme, with four replications. Phenological stages for the application of nitrogen (E1, E3, E4, E5 and E6) and five nitrogen doses (0, 50, 100, 150 and 200 kg ha-1). Nitrogen was applied via the soil using Urea as a source.The following variables were verified: leaf nitrogen content, relative chlorophyll index, and production components: plant height, stem diameter, panicle insertion height, 1000 grain mass, panicle mass, panicle length and productivity. Data were submitted to analysis of combined variance and the means were compared by Tukey test at 5% probability for year of cultivation and application times, and regression analysis was performed for N rates. Statistical analyzes were performed using software R. The year of cultivation of the sorghum crop showed significant influence for almost all evaluated parameters, except panicle insertion. However, for the fertilization application stages, there was no influence on the evaluated parameters. . For the nitrogen doses, there was an influence on the productivity of the growing sorghum.
Keywords: Sorghum bicolor L; Ureia; Produtividade; Safrinha; Nitrogênio; Granifero; Sorghum bicolor L .; Urea; Productivity; Safrinha; Nitrogen; Granifero; CIENCIAS AGRARIAS